Poverty alleviation in developing and underdeveloped countries. Do foreign capital and economic freedom matter? - Han, Qifei; Jin, Lifu; Khan, Muhammad Aamir Shafique; Vitenu-Sackey, Prince Asare; Obrenovic, Bojan (Technological and Economic Development of Economy, 2023)
Our study focuses on the role of foreign capital which includes foreign direct investment, foreign aid, and economic freedom in poverty alleviation in developing and underdeveloped countries by using panel data from 1995 to 2018 for 71 countries. In the pursuit of achieving our objective, we employed several econometric techniques such as dynamic ordinary least square, fully modified ordinary least square, dynamic fixed effect, and pooled mean group regression methods. Furthermore, we performed the Granger causality test, impulse response function, and variance decomposition analysis. In our long-run estimations, we found that foreign direct investment could significantly alleviate poverty but increases poverty in the short run. Instead, foreign aid plays no significant role in poverty alleviation. Moreover, economic growth and economic freedom are essential as our findings consistently exhibited that they play a crucial role in poverty alleviation. We also found bidirectional causality between poverty alleviation and population growth, while a unidirectional causal linkage was found from poverty alleviation to foreign aid. We conclude that policymakers should look at a new paradigm of developmental assistance, and governments should also create an aiding environment for foreign investment to support their growth plan.First published online 13 December 2022